Post a New Question

Algebra

posted by on .

Solve by completing the square:
x^2-6x+3=0


please take me step by step

  • Algebra - ,

    Remember that (a-b)^2 = a^2 - 2ab + b^2

    So, if you have x^2 - 6x you need half of the 6 to complete the square:

    x^2 - 6x + 9 - 9 + 3 = 0
    (x-3)^2 - 6 = 0
    (x-3)^2 = 6

    So, you can see that

    x-3 = ±√6
    so,
    x = 3 ± √6

Answer This Question

First Name:
School Subject:
Answer:

Related Questions

More Related Questions

Post a New Question